Granular refractory material

A granular refractory material with specific compositions and properties addresses the challenge of filling gaps in metal structures while ensuring fire resistance and cable integrity in high-temperature environments.

JP2025008113APending Publication Date: 2025-01-20NICHIAS CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023110003
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing refractory materials do not effectively fill gaps between metal structures while providing fire resistance, especially in environments like nuclear power plants where electric cables are housed within metal housings.

Method used

A granular refractory material composed of metal oxide fine particles with an average particle size of 100 nm or less, a radiation scattering material, and an endothermic material, which includes specific compositions and properties to enhance fillability and fire resistance.

Benefits of technology

The granular refractory material effectively fills gaps between metal structures, providing both excellent filling properties and fire resistance, maintaining cable conductivity and temperature control during high-temperature scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025008113000001_ABST
    Figure 2025008113000001_ABST
Patent Text Reader

Abstract

To provide a granular refractory material with both fillability and fire resistance.SOLUTION: A granular refractory material contains metal oxide fine particles with an average primary particle size of 100 nm or less, a radiation scattering material, and a heat absorbing material. The granular refractory material has a median size of 200 μm or more.SELECTED DRAWING: Figure 1A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a granular refractory material. [Background technology]

[0002] In power plants such as nuclear power plants, it is required to make electric cables fire-resistant. In this regard, Patent Document 1 describes a cable fire protection member that can be wrapped around an electric distribution cable so as to cover the entire circumference in the longitudinal direction, and that has a fire-resistant coating layer applied to at least one side of a fire-resistant cloth made of heat-resistant fiber, in which a heat-foamable fire-resistant coating mainly composed of a flexible resin is applied. In addition, Patent Document 2 describes a cable fire-resistant insulation device that forms a cable fire-resistant insulation structure by covering an electric distribution cable along its longitudinal direction with a fire-resistant insulation layer that is laminated between a first inorganic insulation layer and a second inorganic insulation layer in the thickness direction thereof, with a heat-absorbing layer that absorbs thermal energy and a foaming layer that foams with an increase in temperature to form an insulation layer. In addition, Patent Document 3 describes a heat-absorbing material that includes particles containing magnesium phosphate hydrate and a binder. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2015-089306 A [Patent Document 2] JP 2016-220408 A [Patent Document 3] International Publication No. 2015 / 121894 Summary of the Invention [Problem to be solved by the invention]

[0004] On the other hand, the inventors of the present invention have conducted extensive research, considering that it would be useful to realize a fire-resistant material that has excellent filling properties in gaps in a metal casing (e.g., in a metal double pipe or between metal sheet metal) when, for example, an electrical cable of a power generation plant is installed in the metal casing (e.g., in a metal double pipe or between metal sheet metal).

[0005] The present invention has been made in view of the above problems, and one of its objects is to provide a granular refractory material that combines filling ability and fire resistance. [Means for solving the problem]

[0006] [1] A granular refractory material according to one embodiment of the present invention for solving the above problems includes metal oxide fine particles having an average primary particle size of 100 nm or less, a radiation scattering material, and a heat absorbing material, and has a median diameter of 200 μm or more. According to the present invention, a granular refractory material having both filling ability and fire resistance is provided.

[0007] [2] In the above [1], the granular refractory material has a bulk density of 200 kg / m 3 [3] In the above [1] or [2], the granular refractory material may have a tap density of 300 kg / m or more. 3 [4] In any one of [1] to [3] above, the granular refractory material may have a Hausner ratio of 1.40 or less.

[0008] [5] In any one of [1] to [4] above, the granular refractory material has a crushing strength of 1.60 × 10 as measured by a method in accordance with JIS Z 8841-1993. 6 N / m 2[6] In any of [1] to [5] above, the granular refractory material may have a dust emission rate of particles having a diameter of 0.3 μm or more of 250 pieces / L or less, measured without vibration using a vibration table in a method conforming to JIS B9926-1991. [7] In any of [1] to [6] above, the granular refractory material may have a thermal conductivity of 0.300 W / (m·K) or less at 600°C, measured in a method conforming to ISO 21901:2021.

[0009] [8] In any of the above [1] to [7], the granular refractory material may have a weight loss rate of 30% or less at 25°C to 300°C as measured by differential thermal / thermogravimetric analysis. [9] In any of the above [1] to [8], the granular refractory material may have a volume loss rate of 30% or less when filled in a crucible and fired at 900°C.

[0010]

[10] In any of the above [1] to [9], the metal oxide fine particles may include one or more selected from the group consisting of silica and alumina.

[11] In any of the above [1] to

[10] , the heat absorbing material may include one or more selected from the group consisting of inorganic hydrates and inorganic hydroxides.

[12] In any of the above [1] to

[11] , the heat absorbing material may include one or more selected from the group consisting of phosphate hydrates, sulfate hydrates, fluoride hydrates, Al2(C2O4)3 hydrates, 2MgO·3B2O3 hydrates, Al2O(CO3)2 hydrates, aluminum hydroxide, and lanthanum hydroxide.

[0011]

[13] In any of the above [1] to

[12] , the heat absorption amount of the heat absorption material may be 400 J / g or more.

[14] In any of the above [1] to

[13] , the heat absorption temperature range of the heat absorption material may be in the range of 50°C or more and 500°C or less.

[15] In any of the above [1] to

[14] , the heat absorption start temperature of the heat absorption material may be 500°C or less.

[16] In any of the above [1] to

[15] , the radiation scattering material may include one or more selected from the group consisting of silicon carbide, zirconium silicate, zirconia, iron oxide, iron titanate, and titania.

[0012]

[17] In any of [1] to

[16] above, the granular refractory material may contain 8% by weight or more and 72% by weight or less of the metal oxide fine particles, 2% by weight or more and 18% by weight or less of the radiation scattering material, and 10% by weight or more and 90% by weight or less of the heat absorbing material.

[18] In any of [1] to

[17] above, the granular refractory material may further contain fibers.

[19] In any of [1] to

[18] above, the granular refractory material may be a granular refractory material for filling gaps in a structure. Effect of the Invention

[0013] According to the present invention, there is provided a granular refractory material having both filling properties and fire resistance. [Brief description of the drawings]

[0014] [Figure 1A] FIG. 2 is an explanatory diagram showing an example of the results of observing the granular refractory material according to one embodiment of the present invention with a scanning electron microscope. [Figure 1B] FIG. 4 is an explanatory diagram showing another example of the results of observing the granular refractory material according to one embodiment of the present invention with a scanning electron microscope. [Diagram 2] FIG. 2 is an explanatory diagram showing an example of the results of a fire resistance confirmation test performed on a granular fireproof material according to one embodiment of the present invention. [Diagram 3]FIG. 2 is an explanatory diagram showing an example of a result of evaluating the characteristics of a fireproof material in an example according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] A granular refractory material according to one embodiment of the present invention (hereinafter, referred to as "the refractory material") will be described below. However, the present invention is not limited to this embodiment.

[0016] The present fireproof material is a granular fireproof material containing metal oxide fine particles having an average primary particle size of 100 nm or less, a radiation scattering material, and a heat absorbing material, and having a median diameter of 200 μm or more.

[0017] The metal oxide fine particles contained in the present fireproof material are not particularly limited as long as the average primary particle size is 100 nm or less, and any one type may be used alone or two or more types may be used in any combination.

[0018] The metal oxide fine particles preferably contain at least one selected from the group consisting of, for example, silica and alumina. In this case, it is particularly preferable that the metal oxide fine particles contain silica. When the metal oxide fine particles contain silica, the metal oxide fine particles may further contain alumina or may not contain alumina.

[0019] Specifically, the metal oxide microparticles preferably contain one or more selected from the group consisting of silica microparticles and alumina microparticles, and more preferably contain silica microparticles. When the metal oxide microparticles contain silica microparticles, the metal oxide microparticles may further contain alumina microparticles or may not contain alumina microparticles. When the metal oxide microparticles contain alumina microparticles, the metal oxide microparticles may further contain silica microparticles or may not contain silica microparticles.

[0020] Each of the silica fine particles and the alumina fine particles may be produced by a gas phase method or a wet method, but is preferably produced by a gas phase method.

[0021] That is, the silica fine particles and the alumina fine particles may be dry silica fine particles (e.g., anhydrous silica fine particles) and dry alumina fine particles (e.g., anhydrous alumina fine particles), respectively, or wet silica fine particles and wet alumina fine particles, but the dry silica fine particles and dry alumina fine particles are preferred.

[0022] Furthermore, the silica fine particles and the alumina fine particles may be hydrophilic fumed silica fine particles and hydrophilic fumed alumina fine particles, respectively, or may be hydrophobic fumed silica fine particles and hydrophobic fumed alumina fine particles, respectively, but are preferably hydrophilic silica fine particles and hydrophilic alumina fine particles.

[0023] The silica (SiO2) content of the silica fine particles and the alumina (Al2O3) content of the alumina fine particles are not particularly limited as long as they are within a range in which the effects of the present invention can be obtained, but each is preferably 95% by weight or more, and particularly preferably 98% by weight or more.

[0024] The average particle size of the primary particles of the metal oxide fine particles is not particularly limited as long as it is 100 nm or less, but may be, for example, 90 nm or less, preferably 80 nm or less, more preferably 70 nm or less, even more preferably 60 nm or less, and particularly preferably 50 nm or less. The average particle size of the primary particles of the metal oxide fine particles may be, for example, 1 nm or more, 2 nm or more, 3 nm or more, 4 nm or more, or 5 nm or more. The average particle size of the primary particles of the metal oxide fine particles may be specified by any combination of one of the above-mentioned lower limit values ​​and one of the above-mentioned upper limit values. The average particle size of the primary particles of the metal oxide fine particles is measured by the BET method.

[0025] The metal oxide fine particles preferably have a relatively large specific surface area. That is, the specific surface area of ​​the metal oxide fine particles measured by the BET method is, for example, 50 m 2 / g or more, and 2 / g or more is more preferable, and 200m 2 The specific surface area of ​​the metal oxide fine particles as measured by the BET method is preferably, for example, 400 m 2 / g or less.

[0026] The content of metal oxide microparticles in the present fireproof material (when the present fireproof material contains two or more types of metal oxide microparticles, the total content of the two or more types of metal oxide microparticles) is not particularly limited as long as it is within the range in which the effects of the present invention can be obtained, but may be, for example, 8 wt % or more, preferably 15 wt % or more, more preferably 20 wt % or more, and particularly preferably 25 wt % or more.

[0027] The content of the metal oxide fine particles in the fireproof material may be, for example, 72% by weight or less, 72% by weight or less, 65% by weight or less, 60% by weight or less, 55% by weight or less, 50% by weight or less, 45% by weight or less, or 40% by weight or less. The content of the metal oxide fine particles in the fireproof material may be specified by any combination of one of the above-mentioned lower limit values ​​and one of the above-mentioned upper limit values.

[0028] The radiation scattering material contained in the present fireproof material is not particularly limited as long as it contributes to reducing heat transfer by radiation, and any one type may be used alone or any combination of two or more types may be used. The radiation scattering material is preferably one having far-infrared reflectivity. That is, the radiation scattering material preferably has a relative refractive index of 1.25 or more for light with a wavelength of 1 μm or more. In addition, the radiation scattering material preferably includes one or more selected from the group consisting of silicon carbide, zirconium silicate, zirconia, iron oxide, iron titanate, and titania.

[0029] The shape of the radiation scattering material is not particularly limited, but is preferably particulate. In this case, the average particle size of the radiation scattering material is, for example, preferably 50 μm or less, and particularly preferably 20 μm or less. The average particle size of the radiation scattering material may be, for example, 1 μm or more. The average particle size of the radiation scattering material is measured by a laser diffraction type particle size distribution measuring device.

[0030] The content of radiation scattering material in the present fireproof material (when the present fireproof material contains two or more types of radiation scattering material, the total content of the two or more types of radiation scattering material) is not particularly limited as long as it is within a range in which the effects of the present invention can be obtained, but may be, for example, 2% by weight or more, and is particularly preferably 4% by weight or more.

[0031] The content of the radiation scattering material in the fireproof material may be, for example, 18% by weight or less, and is particularly preferably 10% by weight or less. The content of the radiation scattering material in the fireproof material may be specified by any combination of one of the above-mentioned lower limit values ​​and one of the above-mentioned upper limit values.

[0032] The endothermic material contained in the present fireproof material is not particularly limited as long as it contributes to fireproofing, and any one of them may be used alone or any combination of two or more of them may be used. The endothermic amount of the endothermic material is preferably, for example, 400 J / g or more. That is, the present fireproof material preferably contains an endothermic material having an endothermic amount of 400 J / g or more. The endothermic amount of the endothermic agent is more preferably, for example, 600 J / g or more, and particularly preferably 800 J / g or more. The endothermic amount of the endothermic material may be, for example, 2500 J / g or less. The endothermic amount of the endothermic material is measured by a differential scanning calorimeter (DSC).

[0033] The endothermic temperature range of the endothermic material is preferably, for example, within a range of 50°C or more and 500°C or less. That is, the present fireproof material preferably contains an endothermic material having an endothermic temperature range of 50°C or more and 500°C or less. The endothermic temperature range of the endothermic agent is more preferably, for example, within a range of 65°C or more and 450°C or less, even more preferably within a range of 80°C or more and 400°C or less, and particularly preferably within a range of 90°C or more and 350°C or less. The endothermic temperature range of the endothermic agent is measured by a differential scanning calorimeter (DSC).

[0034] The endothermic material preferably has an endothermic start temperature of, for example, 500°C or less. That is, the present fireproof material preferably includes an endothermic material having an endothermic start temperature of 500°C or less. The endothermic start temperature of the endothermic material is preferably, for example, 300°C or less, more preferably 250°C or less, even more preferably 200°C or less, and particularly preferably 150°C or less. The endothermic start temperature of the endothermic material is preferably, for example, 50°C or more, more preferably 65°C or more, even more preferably 80°C or more, and particularly preferably 90°C or more. The endothermic start temperature of the endothermic material may be specified by arbitrarily combining one of the above-mentioned lower limit values ​​and one of the above-mentioned upper limit values. The endothermic start temperature of the endothermic material is measured by a differential scanning calorimeter (DSC).

[0035] The fireproof material may contain two or more endothermic materials having different endothermic onset temperatures. In this case, the fireproof material preferably contains two or more endothermic materials having an endothermic onset temperature difference of 20° C. or more (for example, a first endothermic material having a first endothermic onset temperature and a second endothermic material having a second endothermic onset temperature 20° C. or more higher than the first endothermic onset temperature), more preferably contains two or more endothermic materials having an endothermic onset temperature difference of 40° C. or more, even more preferably contains two or more endothermic materials having an endothermic onset temperature difference of 60° C. or more, and particularly preferably contains two or more endothermic materials having an endothermic onset temperature difference of 80° C. or more.

[0036] Specifically, the fireproof material may include a first endothermic material having an endothermic onset temperature of 150 ° C or more and a second endothermic material having an endothermic onset temperature of less than 150 ° C., preferably a first endothermic material having an endothermic onset temperature of 160 ° C or more and a second endothermic material having an endothermic onset temperature of 140 ° C or less, more preferably a first endothermic material having an endothermic onset temperature of 170 ° C or more and a second endothermic material having an endothermic onset temperature of 130 ° C or less, even more preferably a first endothermic material having an endothermic onset temperature of 180 ° C or more and a second endothermic material having an endothermic onset temperature of 120 ° C or less, and particularly preferably a first endothermic material having an endothermic onset temperature of 190 ° C or more and a second endothermic material having an endothermic onset temperature of 110 ° C or less.

[0037] The heat absorbing material preferably includes one or more selected from the group consisting of inorganic hydrates and inorganic hydroxides. The inorganic hydrate is preferably one or more selected from the group consisting of phosphate hydrates, sulfate hydrates, fluoride hydrates, Al2(C2O4)3 hydrates (e.g., Al2(C2O4)3·4H2O), 2MgO·3B2O3 hydrates, and Al2O(CO3)2 hydrates.

[0038] The phosphate hydrate may be, for example, one or more selected from the group consisting of magnesium phosphate hydrate (e.g., Mg3(PO4)2·8H2O) and iron phosphate hydrate (e.g., FePO4·2H2O). The sulfate hydrate may be, for example, one or more selected from the group consisting of aluminum sulfate hydrate (e.g., Al2(SO4)3·16H2O) and calcium sulfate hydrate (e.g., CaSO4·2H2O). The fluoride hydrate may be, for example, one or more selected from the group consisting of aluminum fluoride hydrate (e.g., AlF3·3H2O), iron fluoride hydrate (e.g., FeF3·3H2O) and silver fluoride hydrate (e.g., AlF·2H2O). The inorganic hydroxide may be, for example, one or more selected from the group consisting of aluminum hydroxide (Al(OH)3) and lanthanum hydroxide (La(OH)3).

[0039] The content of the endothermic material in the present fireproof material (when the present fireproof material contains two or more types of endothermic materials, the total content of the two or more types of endothermic materials) is not particularly limited as long as it is within a range in which the effects of the present invention can be obtained, and may be, for example, 10% by weight or more, preferably 25% by weight or more, and particularly preferably 40% by weight or more.

[0040] The content of the endothermic material in the present fireproof material may be, for example, 90% by weight or less, preferably 75% by weight or less, and particularly preferably 60% by weight or less. The content of the endothermic material in the present fireproof material may be specified by any combination of one of the above-mentioned lower limit values ​​and one of the above-mentioned upper limit values.

[0041] The fireproof material may further include fibers. The fibers are not particularly limited, and any one type may be used alone or any combination of two or more types may be used. The average fiber length of the fibers is, for example, preferably 0.5 mm or more, and particularly preferably 1 mm or more. The average fiber length of the fibers is, for example, preferably 20 mm or less, and particularly preferably 10 mm or less. The average fiber length of the fibers may be specified by any combination of one of the above-mentioned lower limit values ​​and one of the above-mentioned upper limit values.

[0042] The average fiber diameter of the fibers is, for example, preferably 1 μm or more, and particularly preferably 2 μm or more. The average fiber diameter of the fibers is, for example, preferably 20 μm or less, and particularly preferably 15 μm or less. The average fiber diameter of the fibers may be specified by any combination of one of the above-mentioned lower limit values ​​and one of the above-mentioned upper limit values.

[0043] The fibers may be inorganic fibers, organic fibers, or inorganic and organic fibers, but are preferably inorganic fibers. The inorganic fibers are preferably one or more selected from the group consisting of glass fibers, silica-alumina fibers, silica fibers, alumina fibers, zirconia fibers, alkaline earth metal silicate fibers, rock wool, and basalt fibers, and are particularly preferably one or more selected from the group consisting of glass fibers, silica-alumina fibers, silica fibers, alumina fibers, and alkaline earth metal silicate fibers. The alkaline earth metal silicate fibers are biosoluble inorganic fibers.

[0044] The organic fiber is preferably at least one selected from the group consisting of, for example, aramid fiber, polyethylene fiber, polypropylene fiber, and polyolefin fiber. Regardless of whether the fireproof material contains inorganic fiber or not, the content of organic fiber may be 3% by weight or less, 1% by weight or less, 0.5% by weight or less, 0.2% by weight or less, or 0.1% by weight or less, or may not contain organic fiber (the content of organic fiber is 0% by weight).

[0045] When the present fireproof material contains fibers, the fiber content in the present fireproof material (when the present fireproof material contains two or more types of fibers, the total content of the two or more types of fibers) is not particularly limited as long as it is within a range in which the effects of the present invention can be obtained, but may be, for example, 0.2% by weight or more, and is particularly preferably 1% by weight or more.

[0046] The fiber content in the fireproof material may be, for example, 5% by weight or less, and is particularly preferably 3% by weight or less. The fiber content in the fireproof material may be specified by any combination of one of the above-mentioned lower limit values ​​and one of the above-mentioned upper limit values.

[0047] The present fireproof material preferably contains 30% by weight or less (0% by weight or more, 30% by weight or less) of organic matter (e.g., organic binder such as resin). In this case, the content of organic matter in the present fireproof material is, for example, more preferably 20% by weight or less, even more preferably 15% by weight or less, even more preferably 10% by weight or less, even more preferably 5% by weight or less, even more preferably 1% by weight or less, and may contain no organic matter (organic matter content is 0% by weight).

[0048] The granules constituting the present fireproof material include the above-mentioned metal oxide fine particles, radiation scattering material, and heat absorbing material. The granules constituting the present fireproof material are preferably granulated. That is, the granules constituting the present fireproof material are obtained, for example, by granulating a mixture containing metal oxide fine particles, radiation scattering material, heat absorbing material, and aggregating agent. Specifically, the granules constituting the present fireproof material are preferably granulated containing metal oxide fine particles, radiation scattering material particles, and heat absorbing material particles.

[0049] The median diameter of the present fireproof material is 200 μm or more. The median diameter of the present fireproof material may be, for example, 250 μm or more, 300 μm or more, 350 μm or more, or 400 μm or more. Furthermore, the median diameter of the present fireproof material is, for example, preferably 450 μm or more, more preferably 500 μm or more, even more preferably 550 μm or more, and particularly preferably 600 μm or more.

[0050] The median diameter of the present fireproof material may be, for example, 4000 μm or less, 3500 μm or less, 3000 μm or less, 2500 μm or less, 2000 μm or less, 1500 μm or less, or 1000 μm or less. Furthermore, the median diameter of the present fireproof material is, for example, preferably 900 μm or less, more preferably 850 μm or less, even more preferably 800 μm or less, and particularly preferably 750 μm or less. The median diameter of the present fireproof material may be specified by any combination of one of the above-mentioned lower limit values ​​and one of the above-mentioned upper limit values.

[0051] The median diameter is measured by a method conforming to JIS Z 8825:2013. That is, this median diameter is based on volume, and means that 50% of the particles by volume are smaller than this diameter, and 50% are larger than this diameter. A laser diffraction particle size distribution analyzer is preferably used to measure the median diameter.

[0052] The particle size of the present fireproof material is not particularly limited as long as it is within the range in which the effects of the present invention can be obtained, but may be, for example, 10 μm or more, preferably 100 μm or more, more preferably 200 μm or more, even more preferably 300 μm or more, and particularly preferably 400 μm or more.

[0053] The particle size of the fireproof material may be, for example, 7000 μm or less, preferably 4000 μm or less, more preferably 2000 μm or less, even more preferably 1500 μm or less, and particularly preferably 1200 μm or less. The particle size of the fireproof material may be specified by any combination of one of the above-mentioned lower limit values ​​and one of the above-mentioned upper limit values. The particle size of the fireproof material is measured by a laser diffraction particle size distribution meter.

[0054] This fireproof material has a bulk density of 300 kg / m 3 In this case, the bulk density of the fireproof material may be, for example, 350 kg / m 3More preferably, it is 400 kg / m or more. 3 More preferably, it is 450 kg / m or more. 3 More preferably, it is equal to or greater than this.

[0055] The bulk density of the fireproof material is, for example, 1200 kg / m 3 It may be less than 900 kg / m 3 More preferably, it is equal to or less than 700 kg / m 3 It is particularly preferable that the bulk density of the present fireproof material is equal to or less than 10 ...

[0056] This fireproof material has a tap density of 350 kg / m 3 In this case, the tap density of the present fireproof material may be, for example, 400 kg / m 3 It is preferable that the resistance is 450 kg / m or more. 3 More preferably, it is 500 kg / m or more. 3 More preferably, it is 550 kg / m or more. 3 More preferably, it is equal to or greater than this.

[0057] The tap density of the fireproof material is, for example, 1200 kg / m 3 It may be less than 1000 kg / m 3 It is preferable that the sintering temperature is 900 kg / m or less. 3 More preferably, it is 800 kg / m or less. 3 More preferably, it is equal to or less than 700 kg / m 3 It is particularly preferable that the tap density of the present fireproof material is equal to or less than 1000 nm. The tap density of the present fireproof material may be specified by any combination of one of the above-mentioned lower limit values ​​and one of the above-mentioned upper limit values. The tap density of the present fireproof material is measured by a method in accordance with JIS R 1628-1997.

[0058] The fireproof material may have a Hausner ratio of 1.40 or less. The Hausner ratio of the fireproof material is, for example, preferably 1.33 or less, more preferably 1.30 or less, and particularly preferably 1.25 or less. The Hausner ratio of the fireproof material may be, for example, 1.00 or more, or 1.1 or more. The Hausner ratio of the fireproof material may be specified by any combination of one of the above-mentioned lower limit values ​​and one of the above-mentioned upper limit values. The Hausner ratio of the fireproof material is calculated by dividing the above-mentioned tap density by the above-mentioned bulk density.

[0059] The repose angle of the present fireproof material may be 50° or less. In this case, the repose angle of the present fireproof material is, for example, preferably 45° or less, and particularly preferably 40° or less. The repose angle of the present fireproof material may be, for example, 25° or more, or 30° or more. The repose angle of the present fireproof material may be specified by any combination of one of the above-mentioned lower limit values ​​and one of the above-mentioned upper limit values. The repose angle is measured by the method described in the examples below.

[0060] This fireproof material has a crushing strength of 1.60 x 10, measured according to JIS Z 8841-1993 ("Granular materials - Strength test method"). 6 N / m 2 In this case, the crushing strength of the fireproof material may be, for example, 1.70×10 6 N / m 2 It is preferable that the value is equal to or greater than 1.80×10 6 N / m 2 More preferably, it is 1.90×10 or more. 6 N / m 2 More preferably, it is 2.00×10 or more. 6 N / m 2 It is particularly preferable that the crushing strength of the fireproof material is, for example, 10.00×10 6 N / m 2 It may be the following.

[0061] This fireproofing material may be designed to emit 250 particles / L or less of particles with a diameter of 0.3 μm or more, measured without vibration using a vibration table in accordance with JIS B9926-1991 ("Clean rooms - Measurement method for the amount of dust emitted from the moving mechanism of equipment used").

[0062] In this case, the amount of particles having a diameter of 0.3 μm or more generated by the present fireproof material is, for example, preferably 200 pieces / L or less, and particularly preferably 150 pieces / L or less. The amount of particles having a diameter of 0.3 μm or more generated by the present fireproof material may be, for example, 20 pieces / L or more.

[0063] In addition, the amount of dust generated by this fireproof material of particles having a diameter of 0.5 μm or more is, for example, preferably 100 pieces / L or less, more preferably 80 pieces / L or less, even more preferably 60 pieces / L or less, and particularly preferably 40 pieces / L or less.

[0064] Furthermore, the amount of dust generated by the present fireproof material of particles having a diameter of 1.0 μm or more is, for example, preferably 50 pieces / L or less, more preferably 30 pieces / L or less, and particularly preferably 20 pieces / L or less.

[0065] In addition, the present fireproof material preferably generates, for example, 10 particles / L or less having a diameter of 2.0 μm or more. In addition, the present fireproof material preferably generates, for example, 5 particles / L or less having a diameter of 5.0 μm or more.

[0066] The fireproofing material may have a thermal conductivity of 0.300 W / (m K) or less at 600°C, as measured by a method (periodic heating method) in accordance with ISO 21901:2021 (Thermal insulation - Test method for thermal diffusivity - Periodic heat method).

[0067] In this case, the thermal conductivity of the present fireproof material at 600°C is, for example, preferably 0.250 W / (m·K) or less, more preferably 0.200 W / (m·K) or less, even more preferably 0.190 W / (m·K) or less, and particularly preferably 0.175 W / (m·K) or less. The thermal conductivity of the present fireproof material at 600°C may be, for example, 0.090 W / (m·K) or more.

[0068] The present fireproof material may have a weight loss rate of 30% or less at 25°C to 300°C measured by differential thermal analysis / thermogravimetric analysis. In this case, the weight loss rate of the present fireproof material at 25°C to 300°C is, for example, preferably 28% or less, more preferably 26% or less, and particularly preferably 24% or less. The weight loss rate of the present fireproof material at 25°C to 300°C may be, for example, 5% or more. The weight loss rate of the present fireproof material is measured by a method in accordance with JIS K 0129:2005 (General rules for thermal analysis).

[0069] The present refractory material may have a volume reduction rate of 30% or less when filled in a crucible and fired at 900° C. In this case, the volume reduction rate of the present refractory material when filled in a crucible and fired at 900° C. is, for example, preferably 25% or less, more preferably 20% or less, even more preferably 15% or less, and particularly preferably 12% or less. The volume reduction rate of the present refractory material when filled in a crucible and fired at 900° C. may be, for example, 1% or more.

[0070] The volume reduction rate of the present refractory material when filled in a crucible and fired at 1000° C. may be, for example, 35% or less, preferably 30% or less, more preferably 25% or less, even more preferably 20% or less, and particularly preferably 15% or less. The volume reduction rate of the present refractory material when filled in a crucible and fired at 1000° C. may be, for example, 2% or more.

[0071] The volume reduction rate of the present refractory material when filled in a crucible and fired at 1100°C may be, for example, 50% or less, preferably 40% or less, more preferably 30% or less, even more preferably 25% or less, and particularly preferably 20% or less. The volume reduction rate of the present refractory material when filled in a crucible and fired at 1100°C may be, for example, 3% or more.

[0072] The fireproof material is a granular fireproof material having both filling properties and fire resistance. For this reason, the fireproof material is preferably, for example, a granular fireproof material for filling gaps in a structure. The gap in the structure may be, for example, a gap formed between a first wall and a second wall arranged opposite the first wall. That is, in this case, the structure has a double structure including a first wall and a second wall. The material constituting the first wall and the second wall is not particularly limited, but is preferably an inorganic material. That is, the structure may have, for example, a first wall and a second wall made of metal.

[0073] Specifically, the structure may include, for example, a first plate-like body (corresponding to the first wall) and a second plate-like body (corresponding to the second wall) disposed opposite the first plate-like body. In this case, the fireproof material is preferably used for filling the gap between the first plate-like body and the second plate-like body of the structure. The first plate-like body and / or the second plate-like body may be, for example, a flat plate or a tubular body.

[0074] More specifically, the structure may be, for example, a double pipe including an inner pipe (corresponding to the first wall) and an outer pipe (corresponding to the second wall) housing the inner pipe. In this case, the fireproof material is preferably used for filling the gap between the inner pipe and the outer pipe of the double pipe. The double pipe may be flexible. That is, the double pipe may be a flexible double pipe. The double pipe may also house a cable (e.g., an electric cable). In this case, the double pipe may house the cable in its inner pipe.

[0075] The fireproof material is also preferably used for power plants. In this case, the fireproof material is preferably used for, for example, nuclear power plants. Specifically, the fireproof material is particularly preferably used for gaps in a double structure (for example, the above-mentioned double pipe) of a power plant (for example, a nuclear power plant).

[0076] The fireproof material is produced by a method including forming granules using a raw material including metal oxide fine particles having an average primary particle size of 100 nm or less, a radiation scattering material, and a heat absorbing material. The method for producing the fireproof material preferably includes granulating a raw material including metal oxide fine particles, a radiation scattering material (preferably radiation scattering material particles), and a heat absorbing material (preferably heat absorbing agent particles).

[0077] In this case, the method for producing the fireproof material includes, for example, preparing a raw material mixture containing metal oxide fine particles, a radiation scattering material, a heat absorbing material, and a flocculant, and granulating the raw material mixture. The flocculant is not particularly limited as long as it contributes to granulation, but is preferably one or more selected from the group consisting of water, inorganic flocculants (e.g., aluminum-based flocculants, iron-based flocculants), and organic flocculants (e.g., polymer-based flocculants) (specifically, for example, the group consisting of an aqueous solution containing sugars such as starch, polyacrylamide, polyvinyl alcohol (PVA), polyaluminum chloride (PAC), aluminum sulfate, colloidal silica, wax, lacquer, pitch, clay, slaked lime, and bentonite), and is particularly preferably water. The method for granulating the raw material mixture is not particularly limited as long as it can prepare granules, but is preferably granulated by stirring the raw material mixture, for example.

[0078] In addition, the granulation of the raw material mixture may include removing the flocculant after the formation of the granulated material (for example, after stirring the raw material mixture). The method of removing the flocculant is not particularly limited, but for example, a method of removing the flocculant by drying is preferably used. When removing the flocculant by drying, the drying temperature is preferably lower than the endothermic start temperature of the endothermic agent contained in the granulated material (when the granulated material contains two or more types of endothermic materials, the endothermic start temperature of the endothermic agent having the lowest endothermic start temperature). Specifically, the drying temperature is, for example, preferably 10°C or more lower than the endothermic start temperature of the endothermic agent contained in the granulated material, more preferably 15°C or more lower, and particularly preferably 20°C or more lower.

[0079] In the present method for producing a fireproof material, the raw material mixture to be granulated may include crushed powder of a molded body containing metal oxide fine particles and a radiation scattering material. In this case, in the present method for producing a fireproof material, for example, a raw material mixture containing crushed powder of a molded body containing metal oxide fine particles and a radiation scattering material and a heat absorbing material may be granulated.

[0080] The molded body is not particularly limited as long as it contains metal oxide fine particles and a radiation scattering material, but is preferably, for example, a dry-pressed molded body. The dry-pressed molded body can be obtained, for example, by dry-mixing a raw material containing metal oxide fine particles and a radiation scattering material and dry-pressing the resulting mixture. Such a dry-pressed molded body is preferably produced, for example, by the method described in JP 2012-145217 A. The crushed powder of the molded body can be obtained, for example, by crushing the molded body using a processing device such as a mixer.

[0081] The method for producing the fireproof material may include classifying the granules containing the metal oxide fine particles, the radiation scattering material, and the heat absorbing material. In this case, the granules may be classified to have a particle size of 10 μm or more, preferably 100 μm or more, more preferably 200 μm or more, even more preferably 300 μm or more, and particularly preferably 400 μm or more.

[0082] The granules may be classified so that their particle size is 7000 μm or less, preferably 4000 μm or less, more preferably 2000 μm or less, even more preferably 1500 μm or less, and particularly preferably 1200 μm or less. The particle size of the fireproof material may be classified so that it falls within a range specified by any combination of one of the above-mentioned lower limit values ​​and one of the above-mentioned upper limit values.

[0083] Next, a specific example according to this embodiment will be described. EXAMPLES

[0084] [Manufacturing of granular refractory materials] Anhydrous silica particles with an average primary particle diameter of approximately 13 nm (hydrophilic fumed silica particles, silica content approximately 99.9% by weight, specific surface area approximately 200 m 2 75% by weight of sintered quartz (CuO / g), 20% by weight of silicon carbide (SiC) with an average particle size of 1.8 μm, and 5% by weight of E-glass fiber with an average fiber diameter of 11 μm and an average fiber length of 6 mm were charged into a mixer and mixed in a dry state. The mixture obtained was dry-pressed to obtain a molded body (dry-pressed molded body). Next, the dry-pressed molded body was crushed using a Henschel mixer to obtain granular bodies (crushed powder) with particle sizes of 10 μm to 100 μm.

[0085] Then, 100 parts by weight of the obtained granules and 160 parts by weight of powdered magnesium phosphate octahydrate as a heat absorbing material were put into a Henschel mixer and mixed in a dry state. Furthermore, 160 parts by weight of distilled water as a flocculant was added and mixed to perform granulation.

[0086] The obtained granules were removed from the Henschel mixer and dried for 48 hours at 80° C. After drying, the granules were classified by passing them through a sieve with a mesh size of 1000 μm and a sieve with a mesh size of 500 μm to obtain a granular refractory material having a particle size of 500 μm to 1000 μm.

[0087] [Scanning electron microscope (SEM) observation] The granular refractory material produced as described above was observed by SEM.

[0088] [Manufacturing of double-walled pipes filled with granular refractory material] A flexible double pipe was prepared, which consisted of a 1000 mm long flexible metal inner pipe (diameter approximately 30 mm) and a 1000 mm long flexible metal outer pipe (diameter approximately 113 mm) that houses the inner pipe, and which houses a 1300 mm long electrical cable (diameter approximately 10.5 mm) inside the inner pipe.

[0089] Next, about 4.65 kg of granular fireproofing material was filled into the gap between the inner and outer pipes of the flexible double pipe. Thermocouples (K-type thermocouple (class 2) in JIS 1602) were placed on the surface of the inner pipe and the surface of the electric cable to measure the temperature in the fire resistance confirmation test described later.

[0090] [Fire resistance performance verification test] The flexible double-walled pipe filled with granular fireproofing material as described above was placed in a small heating furnace conforming to "Fire and Disaster Management Agency Notification No. 10: Standards for Fire-Resistant Electric Wires." The center of the flexible double-walled pipe in the longitudinal direction was heated for 60 minutes with a burner (flame temperature approximately 1000°C) to conform to the heating curve of ISO834. During this 60-minute heating period, the temperatures of the inner pipe of the flexible double-walled pipe and the electric cable were measured and recorded using thermocouples.

[0091] [result] 1A and 1B show an example of an SEM photograph of a granular refractory material. As shown in FIG. 1A, the granular refractory material was composed of granulated granules. FIG. 1B shows an enlarged view of one granule. Magnesium phosphate particles were confirmed in the area shown in the white frame in FIG. 1B. It was also confirmed that, in one granule constituting the granular refractory material, magnesium phosphate particles were present not only on the surface of the granule obtained by crushing the dry-pressed compact, but also inside the granule.

[0092] Figure 2 shows the results of measuring the temperature of the inner pipe surface and the temperature of the electric cable surface in the above-mentioned fire resistance confirmation test. In Figure 2, the horizontal axis is heating time (minutes) and the vertical axis is temperature (°C). In Figure 2, the solid line shows the temperature of the electric cable, and the dashed line shows the temperature rise of the inner pipe (the difference between the inner pipe temperature before heating and the inner pipe temperature at each heating time point).

[0093] Here, assuming the inside of a nuclear power plant, the fire resistance standards require that the temperature of the electric cable does not exceed 171.0°C within 60 minutes in the above-mentioned fire resistance performance confirmation test (first fire resistance standard), and that the temperature difference (temperature rise) before and after the experiment is 140.0°C or less (second fire resistance standard).

[0094] In this regard, as shown in Figure 2, at the point of 60 minutes of heating, the temperature of the electric cable was 128.5°C, and the temperature rise of the inner tube was 131.4°C. In other words, it was confirmed that the double-walled pipe filled with granular fire-resistant material met both the first and second fire resistance standards. In addition, the conductivity of the electric cable housed in the inner tube of the flexible double-walled pipe was maintained even after the fire resistance performance confirmation test. EXAMPLES

[0095] [Example 2-1] A granular refractory material was produced in the same manner as in Example 1 above.

[0096] [Example 2-2] A granular refractory material was produced in the same manner as in Example 1 above, except that 160 parts by weight of powdered magnesium phosphate octahydrate and 40 parts by weight of powdered aluminum hydroxide were used as the heat absorbing material.

[0097] [Comparative Example 2-1] 100 parts by weight of powdered magnesium phosphate octahydrate as a heat absorbing material and 10% by weight of water glass as a flocculant were mixed and granulated, and then dried to obtain particles.

[0098] [Comparative Example 2-2] 75 parts by weight of anhydrous silica fine particles (hydrophilic fumed silica fine particles) with an average primary particle size of approximately 13 nm, 20 parts by weight of silicon carbide (SiC) with an average particle size of 1.8 μm, 5 parts by weight of E-glass fibers with an average fiber diameter of 11 μm and an average fiber length of 6 mm, 160 parts by weight of powdered magnesium phosphate octahydrate, and 40 parts by weight of powdered aluminum hydroxide were charged into a Henschel mixer and mixed in a dry state to obtain a powdered refractory material.

[0099] [Median diameter] For each of the fireproof materials manufactured as described above, the median diameter was measured using a laser diffraction particle size distribution analyzer according to a method conforming to JIS Z 8825: 2013. Samples were taken three times for each fireproof material, the median diameter of each sample was measured, and the arithmetic average of the three measured values ​​was taken as the median diameter.

[0100] [Bulk density, tapped density, Hausner ratio] The bulk density and tap density of each refractory material were measured using a measuring cylinder according to JIS R 1628-1997 ("Method of measuring bulk density of fine ceramic powders"). The Hausner ratio was calculated using the following formula: Hausner ratio (-) = tap density (kg / m 3 ) ÷ Bulk density (kg / m 3 ).

[0101] [Angle of repose] The angle of repose of each refractory material was measured using a protractor.

[0102] [Crushing strength] The crushing strength of each of the granular refractory materials of Examples 2-1, 2-2, and Comparative Example 2-1 was measured using an autograph (AGX-100kNV, manufactured by Shimadzu Corporation) in accordance with JIS Z 8841-1993 ("Granular products - Strength test method"). Here, the crushing strength Sc (N / m of the granule in a test in which a load P (N) was applied to a granule with a diameter D (m) was 2 ) is calculated by the following formula: Sc = 4 × P ÷ (π × D 2The diameter D (m) of the granules was 0.766 mm. It should be noted that it was difficult to measure the crushing strength of the fireproof material of Comparative Example 2-2 because it was in a powder form.

[0103] [Amount of dust generated] For each fireproofing material, the amount of dust generated was measured in a clean room without vibration using a vibration table, in accordance with JIS B9926-1991 ("Clean room - Method for measuring the amount of dust generated from the moving mechanism of the equipment used").

[0104] Specifically, a vat (250 mm x 170 mm, depth 20 mm) containing fireproofing material was placed in a chamber equipped with a HEPA filter, and purified air was passed through it at a speed of 0.6 m / s. The concentration of particles generated from the fireproofing material in the vat was then measured by a particle counter near the exhaust port of the chamber.

[0105] [Thermal Conductivity] Each refractory material was dried at 300°C for 48 hours, and then its thermal conductivity at 600°C was measured using a method in accordance with ISO 21901:2021 (cyclic heating method).

[0106] [Weight reduction rate] For each refractory material, the weight loss rate when heated from 25°C to 300°C at a heating rate of 5°C / min was measured using a simultaneous differential thermal and thermogravimetric analyzer (TG8120, Rigaku Corporation) in accordance with JIS K 0129:2005 (General rules for thermal analysis) (thermogravimetry-differential thermal (TG-DTA) measurement).

[0107] [Volume reduction rate] For each refractory material, a crucible (inner diameter approx. 65 mm, depth approx. 50 mm, volume approx. 150,000 mm) was used. 3The volume reduction rate was measured when the refractory material was filled in a crucible and fired at 900°C. That is, the refractory material was filled up to the height of the edge of the crucible, and then each refractory material was heated together with the crucible in an electric furnace at 900°C for 180 minutes and fired. After firing, the reduced height of the refractory material filled in the crucible was measured. The volume reduction rate (%) of the refractory material was measured by the following formula: Volume reduction rate (%) = {(height of refractory material before firing) - (height of refractory material after firing)} x (diameter of crucible) ÷ (volume of crucible) x 100. Similarly, the volume reduction rate was also measured when the refractory material was fired at 1000°C and when it was fired at 1100°C.

[0108] [result] FIG. 3 shows the results of evaluating the median diameter, bulk density, tapped density, Hausner ratio, angle of repose, crushing strength, thermal conductivity, weight reduction rate, volume reduction rate, and dust generation amount for each refractory material as described above.

[0109] As shown in FIG. 3, the median diameters of the granular refractory materials of Examples 2-1 and 2-2 were 641 μm and 694 μm, respectively, whereas the median diameter of the granular refractory material of Comparative Example 2-1 was significantly larger at 4735 μm, and the median diameter of the powdered refractory material of Comparative Example 2-2 was significantly smaller at 172 μm.

[0110] The bulk density and tap density of the granular refractory materials of Examples 2-1 and 2-2 and Comparative Example 2-1 were almost the same, whereas those of the powdered refractory material of Comparative Example 2-2 were significantly smaller.

[0111] Furthermore, the Hausner ratios of the granular refractory materials of Examples 2-1 and 2-2 were 1.16 and 1.20, respectively, and the Hausner ratio of the granular refractory material of Comparative Example 2-1 was 1.06, while the Hausner ratio of the powdery refractory material of Comparative Example 2-2 was significantly larger at 1.46. In general, a Hausner ratio of 1.25 or less is considered to have good fluidity, whereas a Hausner ratio of 1.34 or more is considered to have poor fluidity.

[0112] The angles of repose of the granular refractory materials of Examples 2-1 and 2-2 were 33° to 34° and 35° to 37°, respectively, and those of the granular refractory material of Comparative Example 2-1 were 24° to 28°, whereas the Hausner ratio of the powdered refractory material of Comparative Example 2-2 was significantly large at 55° to 60°. Generally, a repose angle of 40° or less is considered to have good fluidity, whereas a repose angle of 46° or more is considered to have poor fluidity.

[0113] The crushing strength of the granular refractory materials of Examples 2-1 and 2-2 was significantly higher than that of the granular refractory material of Comparative Example 2-1. The thermal conductivity at 600°C of the granular refractory materials of Examples 2-1 and 2-2 was significantly lower than that of the granular refractory material of Comparative Example 2-1.

[0114] The weight loss rate at 600°C of the granular refractory materials of Examples 2-1 and 2-2 was 22%, which was significantly smaller than that of the granular refractory material of Comparative Example 2-1. The volume loss rates of the granular refractory materials of Examples 2-1 and 2-2 after firing at 900°C, 1000°C, and 1100°C were all significantly smaller than those of the granular refractory material of Comparative Example 2-1 and the powdery refractory material of Comparative Example 2-2. The amount of dust generated by the granular refractory materials of Examples 2-1 and 2-2 was significantly smaller than that of the granular refractory material of Comparative Example 2-1 and the powdery refractory material of Comparative Example 2-2.

Claims

1. Metal oxide fine particles having an average primary particle size of 100 nm or less; A radiation scattering material; A heat absorbing material; Including, The median diameter is 200 μm or more. Granular refractory material.

2. Bulk density: 300 kg / m 3 That's all.

2. The granular refractory material according to claim 1.

3. Tap density: 350 kg / m 3 That's all. The granular refractory material according to claim 1.

4. The Hausner ratio is 1.40 or less.

2. The granular refractory material according to claim 1.

5. The crushing strength measured according to JIS Z 8841-1993 is 1.60 x 10 6 N / m 2 That's all.

2. The granular refractory material according to claim 1.

6. The amount of particles with a diameter of 0.3 μm or more measured without vibration using a vibration table in accordance with JIS B9926-1991 is 250 pieces / L or less.

2. The granular refractory material according to claim 1.

7. The thermal conductivity at 600°C measured by a method conforming to ISO 21901:2021 is 0.300 W / (m K) or less; 2. The granular refractory material according to claim 1.

8. The weight loss rate at 25°C to 300°C measured by differential thermal analysis or thermogravimetric analysis is 30% or less. The granular refractory material according to claim 1.

9. When filled into a crucible and fired at 900°C, the volume reduction rate is 30% or less. The granular refractory material according to claim 1.

10. The metal oxide fine particles include one or more selected from the group consisting of silica and alumina.

2. The granular refractory material according to claim 1.

11. The heat absorbing material includes one or more selected from the group consisting of inorganic hydrates and inorganic hydroxides. The granular refractory material according to claim 1.

12. The heat absorbing material is a phosphate hydrate, a sulfate hydrate, a fluoride hydrate, Al 2 (C 2 O 4 ) 3 Hydrate of 2MgO.3B 2 O 3 Hydrate of Al 2 O (CO 3 ) 2 hydrate, aluminum hydroxide, and lanthanum hydroxide, 2. The granular refractory material according to claim 1.

13. The heat absorption amount of the heat absorption material is 400 J / g or more. The granular refractory material according to claim 1.

14. The endothermic temperature range of the endothermic material is in the range of 50° C. or more and 500° C. or less.

2. The granular refractory material according to claim 1.

15. The endothermic material has an endothermic start temperature of 500° C. or less. The granular refractory material according to claim 1.

16. The radiation scattering material includes one or more selected from the group consisting of silicon carbide, zirconium silicate, zirconia, iron oxide, iron titanate, and titania.

2. The granular refractory material according to claim 1.

17. 8% by weight or more and 72% by weight or less of the metal oxide fine particles; 2% by weight or more and 18% by weight or less of the radiation scattering material; 10% by weight or more and 90% by weight or less of the heat absorbing material; The granular refractory material according to claim 1.

18. Further comprising fibers, The granular refractory material according to claim 1.

19. A granular fireproofing material for filling gaps in structures.

2. The granular refractory material according to claim 1.

Citation Information

Patent Citations

  • Cable fireproof member and fireproof facility

    JP2015089306A

  • Cable fireproof heat insulation device

    JP2016220408A

  • Heat-absorbing material that uses magnesium phosphate hydrate

    WO2015121894A1